Association between Alanine Aminotransferase and Growth Hormone: A Retrospective Cohort Study of Short Children and Adolescents. (3rd April 2019) - Ji, Baolan; Zhang, Mei; Zhao, Qianqian; Chu, Yuntian; Li, Yanying; Pan, Hui; Ban, Bo
Abstract : Objective. This study aimed to examine the relationship between serum alanine aminotransferase (ALT) and growth hormone (GH) in children and adolescents with short stature. Methods. In this retrospective cohort study, 670 Chinese children and adolescents with short stature were included, and 253 of them received recombinant human GH (rhGH) therapy. Anthropometric and biochemical indicators were measured. GH peak levels were assessed after provocation tests with L-dopa and insulin. The subjects were divided into 3 groups according to the GH peak level. The association between the GH peak and ALT was analyzed. The change of ALT during rhGH therapy was assessed by a generalized additive mixed model. Results . Serum ALT and incidence of ALT elevation were both decreased across the GH tertiles ( P = 0.002, 0.012, respectively). A univariate analysis showed that the GH peak was negatively associated with ALT ( β : -0.12; 95%CI: -0.22, -0.02; P = 0.023). Furthermore, multiple linear stepwise regression analysis demonstrated that the GH peak was independently related to ALT after adjusting for other confounding variables ( β : -0.12; 95%CI: -0.24, -0.00; P = 0.042). Besides, mean values of the change in ALT from baseline displayed that, during the early stages of rhGH treatment, serum ALT level indicated a temporary upward trend, but it subsequently gradually decreased ( β : -0.16; 95%CI: -0.23, -0.09; P < 0.001). Conclusions. GH secretion level was strongly negatively correlated with ALT in short children and adolescents. And rhGH therapy could reduce ALT level over time.